Project based-injected learning for reading development: A classroom action research in senior EFL classes - Liando, Nihta Vera Frelly; Tatipang, Devilito Prasetyo; Ismail, Ismail (UPT Bahasa Universitas Tanjungpura, 2025)
This study investigates the impact of Project-Based Learning (PBL) on enhancing senior high school students’ reading aloud and narrative writing skills in an English as a Foreign Language (EFL) context. Conducted through Classroom Action Research (CAR) over two cycles with 50 students in North Sulawesi, Indonesia, the research applied a randomized class sampling technique. Data were collected using reading aloud assessments, narrative text rubrics, observations, and documentation. Quantitative analysis revealed significant improvements in students’ reading performance across categories including pronunciation, fluidity, volume, and intonation, with the proportion of students rated Excellent increasing notably from Cycle I to Cycle II (e.g., pronunciation from 14% to 34%). Narrative writing scores also rose substantially, with most students achieving mastery-level performance in the second cycle. Qualitative findings indicated heightened student engagement, motivation, and collaboration as a result of the PBL implementation. Challenges remained for a small subset of students with persistent low performance, potentially influenced by individual motivation and linguistic background. The study confirms that PBL effectively promotes active learning and measurable gains in English reading skills, supporting the integration of project-centered activities in EFL classrooms. Pedagogical implications include the need for teachers to design project tasks that foster student autonomy and provide opportunities for meaningful language practice. Future research should explore digital PBL platforms and broader, cross-institutional studies to validate and extend these findings. This research contributes original evidence of PBL’s value in developing both oral and written reading proficiency, offering practical insights for Indonesian EFL education. How to cite this article: Liando, N. F., Tatipang, D. P., & Ismail. (2025). Project based-injected learning for reading development: A classroom action research in senior EFL classes. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(2), 106-130. http://dx.doi.org/10.26418/jeltim.v7i2.98983